2020
DOI: 10.1002/cbdv.202000575
|View full text |Cite
|
Sign up to set email alerts
|

Chemodiversity and Antibacterial Activity of the Essential Oil of Leaves of Croton argyrophyllus

Abstract: The Croton argyrophyllus leaf essential oil has anti-inflammatory, antioxidant, cytotoxic among other activities. However, there are chemical composition variations in the literature. This work reports the first study of the intraspecific chemical variation of C. argyrophyllus population from Pernambuco state, Brazil. The essential oils of nine specimens (OCA1 to OCA9) were analyzed by GC/MS and NIR to identify the chemical compositions and to verify the similarities between the analyzed samples. These analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Compared to data reported in the literature, de Araújo et al [ 16 ] obtained MIC results greater than 1024 μg/mL, indicating that it is not clinically relevant. On the other hand, de Araújo et al [ 24 ] reported that the EO from C. heliotropiifolius Kunth presented inhibitory activity against Bacillus subtilis and Staphylococcus aureus , and de Araújo et al [ 25 ] reported inhibitory activity against Staphylococcus aureus by the EO from C. argyrophyllus .…”
Section: Discussionmentioning
confidence: 99%
“…Compared to data reported in the literature, de Araújo et al [ 16 ] obtained MIC results greater than 1024 μg/mL, indicating that it is not clinically relevant. On the other hand, de Araújo et al [ 24 ] reported that the EO from C. heliotropiifolius Kunth presented inhibitory activity against Bacillus subtilis and Staphylococcus aureus , and de Araújo et al [ 25 ] reported inhibitory activity against Staphylococcus aureus by the EO from C. argyrophyllus .…”
Section: Discussionmentioning
confidence: 99%
“…For phenols, values of 245 μg·mg −1 in J. mollissima leaf extract [ 26 ] and 58.07 mg·g −1 in its latex [ 27 ] are reported; these results differ from the results from the concentrations obtained here. Such differences can be explained by the difference in the parts of the plant used to prepare the extracts (leaves, flowers, bark, roots and latex) [ 48 , 49 ] and due to the vegetative cycle, botanical origin and climatic factors [ 50 ]. Therefore, the results confirmed the presence of the class of phenols, flavonoids and tannins metabolites in the EEJM, highlighting the tannins which presented a concentration of 431.68 mg·g -1 and may be one of the main groups of compounds responsible for the biological activities of J. mollissima latex.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, it was possible to identify and quantify 70 different chemical compounds, of which the monoterpenes 1,8 cineole (13.15%) and p-cymene (10.68%) were the majority, as well as the sesquiterpenes caryophyllene (9.73%) and spathulenol (6.36%). This variation in the chemical composition of the EOCC may be related to factors such as the specific location of leaf collection, growing season, botanical origin, climatic factors [ 25 ] and the drying process that was used on the plant material.…”
Section: Resultsmentioning
confidence: 99%